DIAGNOSIS KESULITAN BELAJAR MAHASISWA PENDIDIKAN GURU MADRASAH IBTIDAIYAH PADA MATA KULIAH PEMBELAJARAN IPA DI FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Hairiah, Muslimatul; Yaumi, Muhammad; Safe, Safe; Basam, Fajri (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2022)
This paper is the result of research that discusses the diagnosis of learning difficulties for students of Madrasah Ibtidaiyah teacher education in science learning courses at the Tarbiyah and Teacher Training Faculty of UIN Alauddin Makassar. This study has the objectives to: 1) describe the form of learning difficulties for madrasah ibtidaiyah teacher education students in science learning courses at the tarbiyah and Teacher Training Faculty of UIN Alauddin Makassar, 2) provide solutions in overcoming learning difficulties for madrasah ibtidaiyah teacher education students in science learning courses at Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar. The type of research used is Descriptive qualitative, the subject of this research is ten students of madrasah ibtidaiyah teacher education. The results of the descriptive research show that the difficulty in understanding the science material itself is still lacking, besides that the facilities in studying science are still inadequate. Then the factors of learning difficulties are students understanding of science material which is still lacking, pratikum implementation is still not implemented, and learning methods are still less effective. And the solution in overcoming learning difficulties is that lecturers should always provide motivation to students who have difficulty learning science, lecturers should also provide training to read scientific terms and provide guidance on how to use laboratories, science laboratory facilities majoring in madrasah ibtidaiyah teacher education at the Tarbiyah and Teacher Training Faculty UIN Alauddin Makassar was held.